Papel da fotobiomodulação vascular por luz de diodo vermelha em modelo experimental de asma induzida por ovoalbumina - Alonso, Paula Tatiane (2021)
Asthma is a chronic inflammatory disease characterized by recurrent and reversible episodes of wheezing, dyspnea, chest stiffness, and cough. Its treatment includes several drugs, high cost, and considerable side effects. Photobiomodulation (PBM) emerges as an alternative treatment, showing good results, and it can be applied locally or systemically. We evaluated the effect of Vascular Photobiomodulation (VPBM) by Light Emitting Diode (LED) in the course of asthma. Adult rats were sensitized and challenged or not with ovalbumin (OVA) plus alum for induction of asthma and irradiated or not with VPBM in the caudal artery (Power: 100mW; Wavelength 660 ± 10 nm; Total radiant emission 15 J; Spot Size: 2,8 cm2; Energy density at aperture: 5,35 J/cm2; Irradiance: 33,3 mW/cm2; Total time: 150 s). Our investigations prioritized the cell migration into the alveolar space and lung, tracheal responsiveness, release and gene expression of cytokines, mast cell degranulation, and anaphylactic antibodies. Our results showed that VPBM reduced the cell migration and mast cell degranulation without altering the tracheal responsiveness and ovalbumin antibody titers. The VPBM increased the levels of interleukin 10 (IL-10) in the bronchoalveolar lavage fluid without altering the gene expression of cytokines in the lung tissue. Thus, the VPBM reduced lung inflammation by altering mast cells degranulation and IL-10 level. Considering that this study is a pioneer in the used of Light Emitting Diode (LED) by the systemic route to treat asthma, the data are interesting and instigate future investigations, mainly in relation to the mechanisms involved and in dosimetry.